Clinical and functional outcome of elastic stable intramedullary nailing in pediatric femoral fractures in the age group of 5-16 years - Edwin, Ajin; I., Ibad Sha; R., Roshna S.; Shah, Namitha (International Journal of Research in Orthopaedics, 2020)
Background: Fractures of the femur are the most incapacitating fractures. The best treatment for children between five to sixteen years of age is still debated. The ESIN has the benefits of early immediate stability to the involved bone segment, permitting early mobilization and return to the normal activities of the patients, respect for the physes, minimal scarring with lower complications. The purpose of this study was to present this study results following fixation of femoral shaft fractures with titanium elastic nails between the age 5-16 years of age. Methods: A total 52 patients in the age group of 5-16 years with femoral shaft fractures were stabilized using flexible nailing. Clinical and radiological follow-up was for a minimum period of 24 months. The final results were analysed using Flynn’s criteria. Results: Mean age at surgery was 7.4 years (range 5.6-14.3 years). The average duration of surgery was 65.3 (45-95) minutes and the mean duration of hospital stay was 8 (5-14) days. Skin irritation due to nail ends was the most common complication followed by significant lengthening (n=6), infection (n=2), significant shortening (n=2), varus angulation (n=2) and delayed union (n=2). The final outcome was excellent in 65.4% cases, satisfactory in 30.8% cases and three patients had poor outcomes as per Flynn's scoring criteria. Conclusions: In this study, ESIN showed good clinical and radiographic results in the age group 5 to 16 years, with minimal complications and high parent satisfaction consistent with previous studies but lesser number of mid adolescent age groups in the present study is a limitation.